2016
DOI: 10.18632/oncotarget.11832
|View full text |Cite
|
Sign up to set email alerts
|

Heparins that block VEGF-A-mediated von Willebrand factor fiber generation are potent inhibitors of hematogenous but not lymphatic metastasis

Abstract: Von Willebrand factor (VWF) serves as a nidus for platelet aggregation and thrombosis. We hypothesize that VWF fibers contribute to the development of venous thromboembolism (VTE) and to metastasis formation. Here, we show that vascular and lymphatic endothelial cells (ECs) express VWF in vitro and release VWF fibers after activation by tumor cell supernatants. In contrast, an ex vivo analysis of primary mouse tumors revealed the presence of VWF fibers in the blood microvasculature but not in lymphatic vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 67 publications
4
53
0
1
Order By: Relevance
“…Besides the antithrombotic impact of LMWHs, accumulating clinical evidence suggests that LMWH significantly improve disease progression and OS directly by its antitumor effect. Indeed, in vitro and in vivo studies also from our group have shown that LMWHs could influence angiogenesis, cancer cell adhesion, tumor cell proliferation, local tumor growth and metastases through a number of coagulation‐independent mechanisms …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides the antithrombotic impact of LMWHs, accumulating clinical evidence suggests that LMWH significantly improve disease progression and OS directly by its antitumor effect. Indeed, in vitro and in vivo studies also from our group have shown that LMWHs could influence angiogenesis, cancer cell adhesion, tumor cell proliferation, local tumor growth and metastases through a number of coagulation‐independent mechanisms …”
Section: Discussionmentioning
confidence: 98%
“…In order to address the problem of activated coagulation in cancer patients several studies have focused on the effect of heparin on tumor progression . Recent clinical studies have demonstrated an inhibitory effect of low molecular weight heparins (LMWH) on tumor growth and metastasis, resulting in a beneficial effect on the survival of cancer patients …”
mentioning
confidence: 99%
“…41 We generated primary melanomas characterized by well-defined disease progression and active luminal VWF secretion from the endothelium. 4,42 Our previous studies already suggested potential cross talk between VWF and the endothelial glycocalyx because therapy with the low molecular-weight heparin tinzaparin blocked the formation of VWF fiber networks in tumor-bearing mice. Suppressed fiber formation was associated with a reduced tumor-cell progression, underlining the potential biological relevance of an endothelial glycocalyx-mediated anchorage of VWF.…”
Section: Discussionmentioning
confidence: 98%
“…As a mechanistic explanation of this association it was hypothesized that cancer‐related VTE may be based on VWF‐mediated platelet aggregation . Bauer et al recently demonstrated in vitro that melanoma cells can activate vascular endothelial cells and prompt them to release ULVWF which is followed by platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this study both VWF−/− and ADAMTS‐13−/− mice showed more metastatic lung foci. The authors hypothesize that VWF‐deficient mice come with further alteration of endothelial cell physiology (like missing Weibel palade bodies and dysregulated secretion of pro‐metastatic factors), which may be responsible for the increased metastatic potential …”
Section: Discussionmentioning
confidence: 99%